2022
DOI: 10.1101/2022.02.02.22270351
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Real world performance of inactivated SARS-CoV-2 vaccine (CoronaVac) against infection, hospitalization and death due to COVID-19 in adult population in Indonesia

Abstract: Background: Inactivated SARS-CoV-2 vaccine has been included in the national COVID-19 vaccination program in Indonesia since January 2021. The study aims to estimate the effectiveness of CoronaVac vaccine in preventing SARS-CoV-2 infection, hospitalization, and death in adult population aged ≥18 years in Bali, Indonesia. Methods: Test-negative, case control study was conducted by linking SARS-CoV-2 laboratory records, COVID-19 vaccination, and health administrative data for the period of January 13 to June 30,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
3
2
Order By: Relevance
“…The effectiveness against hospitalization in this study, in contrast, is higher than those from test-negative case-control studies in Brazil, China, and Indonesia (VE, 55%–71%) [ 6 , 7 , 9 ]. The different results about the VE for the same vaccine between this and previously published studies might be due to the variations in demographics of study populations and the sampling time frame vis-à-vis SARS-CoV-2 variants.…”
Section: Discussioncontrasting
confidence: 89%
See 2 more Smart Citations
“…The effectiveness against hospitalization in this study, in contrast, is higher than those from test-negative case-control studies in Brazil, China, and Indonesia (VE, 55%–71%) [ 6 , 7 , 9 ]. The different results about the VE for the same vaccine between this and previously published studies might be due to the variations in demographics of study populations and the sampling time frame vis-à-vis SARS-CoV-2 variants.…”
Section: Discussioncontrasting
confidence: 89%
“…Partial vaccination also offered protections against symptomatic infection by 49% and hospitalization by 75%, but these estimates have wider confidence intervals compared to those for full vaccination given the smaller numbers of persons who were only partially vaccinated. The effectiveness of full vaccination against symptomatic infection in this study is slightly lower than those of the CoronaVac vaccine from other test-negative case-control studies conducted in Brazil and China (VE range, 36%–67%) [ 6–9 ] or prospective cohort study in Chile (VE, 66%) [ 5 ]. The protection rate against symptomatic infection is also lower than the efficacies of the CoronaVac vaccine from phase 3 randomized clinical trials conducted in Turkey, Brazil, and Indonesia (50%–83%) [ 10–12 ].…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…22 Limited observational evidence suggests strong and durable protection against severe disease and death, with transient protection against milder symptomatic disease. [23][24][25][26] With a largely infection-naïve population and two COVID-19 vaccines in widespread use, Hong Kong represents a unique environment for monitoring vaccine effectiveness (VE) against Omicron BA.2. In this study we estimated VE of one, two and three doses of BNT162b2 and CoronaVac, their relative effectiveness, and the additional protection offered by third doses against mild/moderate infections, severe/fatal disease and death.…”
Section: Introductionmentioning
confidence: 99%
“…Breakthrough infections have been examined in Indonesia. A test-negative case-control study conducted in Bali, Indonesia revealed that CoronaVac was 71.1% effective in preventing hospitalization and 87.4% effective in preventing death in participants at least 18 years of age [19]. However, research involving real-world models of COVID-19 vaccine effectiveness in Indonesia is still limited.…”
Section: Introductionmentioning
confidence: 99%